Enhancing the low temperature water-gas shift reaction through a hybrid sorption-enhanced membrane reactor for high-purity hydrogen production - Luís M. Madeira (2015)
The low temperature water-gas-shift reaction (LT-WGS) has been assessed by means of a hybrid sorption-enhanced membrane reactor (HSEMR) that combines both CO2 and H-2 removal from the reaction zone. The performance of this reactor has been compared with that obtained by (i) a traditional and (ii) a sorption-enhanced (only CO2 is removed) reactor operating in the same operational conditions. Cu/ZnO-Al2O3 and K2CO3-promoted hydrotalcite materials have been used as a catalyst and CO2 sorbent, respectively. A self-supported Pd-Ag membrane tube has been used in order to selectively separate the H-2. The CO2 sorption capacity, in the presence and absence of water vapour, of the potassium-promoted hydrotalcite has been determined by means of breakthrough experiments. The presence of water vapour enhanced the sorption capacity of the hydrotalcite in the experimental conditions used. Concerning the performance of the HSERM, results clearly show that when both CO2 and H-2 are removed from the reaction zone, the hydrogen production through the reversible LT-WGS reaction is enhanced compared to either a traditional or a sorption-enhanced reactor, allowing overcoming equilibrium limitations and obtain a pure H-2 stream.